REFRAMING IN CONFLICT MEDIATION: EMPOWERING PARTIES OR MANIPULATING DECISION-MAKING? - Anam, Syaiful; Satris, Rezki (Universitas Muhammadiyah Yogyakarta, 2020)
This study aims to explain how to reconstruct the form of mediation through a framing analysis. The concept of framing in mediation is a form of communication that is constructively framed. The dynamics of conflict, the mediation process becomes the most decisive part of the problem-solving process. How a mediator is able to reframe this mediation concept by empowering the conflicting parties to get out of the problem without having to worsen the situation. The research method used qualitative with a framing analysis approach that explains of a mediator is not a decision-maker in the negotiation process. A mediator is able to find solutions to constructive and cooperative problems in accordance with the mediator's abilities.